ANORECTAL MALFORMATIONS: FUNCTIONAL OUTCOME OF POSTERIOR SAGITTAL ANORECTOPLASTY - Khan, Kifayat; Khan, Muhammad Jehangir; Khan, Muhammad Younas (Journal of Postgraduate Medical Institute, 2011)
Objective: To assess the functional outcome of patients with anorectal malformations treated with Posterior Sagittal Anorectoplasty (PSARP). Material and Methods: This study was conducted on 355 patients with anorectal malformations at Lady Reading Hospital, Peshawar from July 1998 to July 2004. Distal loopogram was performed routinely in all patients except the female patients with rectogenital tract fistula. PSARP was performed in all the patients with intermediate, high type and cloacal malformations. Operative and postoperative mortality and morbidity was recorded. Regular anal dilatation was advised after discharge, which was continued for 3-6 months after the PSARP procedure. Patients were followed up for 6-12 months. Results: Study included 355 patients (245 boys and 110 girls) ranging in age from 12-36 months. PSARP was performed in all the patients. There were 195 boys with rectourethral fistula and 95 girls with genitourinary tract fistula while 5 girls had cloacal malformations. Operative and postoperative mortality was 9/355 (2.5%). Early functional results were good in 30%, fair in 45% and poor in 25% patients. Chronic constipation and anal stenosis was found in 99 and 35 patients respectively. Mucosal prolapse with perineal itching was present in 60 patients. Recurrent UTI and orchitis was found in 5 and 3 patients respectively. Urethral stricture and urethral diverticulum was found in two cases each, while redo surgery was performed in two patients. Conclusion: The incidence of high and intermediate anorectal anomalies was more in male babies. The PSARP procedure is safe with good functional results in terms of faecal continence.